Self-assembly of helical ribbons - Zastavker, Yevgeniya V. (The National Academy of Sciences, 1999)
The self-assembly of helical ribbons is examined in a variety of multicomponent enantiomerically pure systems that contain a bile salt or a nonionic detergent, a phosphatidylcholine or a fatty acid, and a steroid analog of cholesterol. In almost all systems, two different pitch types of helical ribbons are observed: high pitch, with a pitch angle of 54 ± 2°, and low pitch, with a pitch angle of 11 ± 2°. Although the majority of these helices are right-handed, a small proportion of left-handed helices is observed. Additionally, a third type of helical ribbon, with a pitch angle in the range 30–47°, is occasionally found. These experimental findings suggest that the helical ribbons are crystalline rather than liquid crystal in nature and also suggest that molecular chirality may not be the determining factor in helix formation. The large yields of helices produced will permit a systematic investigation of their individual kinetic evolution and their elastic moduli.